Coexistence of Spin Canting and Metamagnetism in a One-Dimensional Mn(II) Compound Bridged by Alternating Double End-to-End and Double End-On Azido Ligands and the Analog Co(II) Compound - Nesrine Benamara; Zouaoui Setifi; Chen-I Yang; Sylvain Bernès; David K. Geiger; Güneş Süheyla Kürkçüoğlu; Fatima Setifi; Jan Reedijk (Magnetochemistry, 2021)
Two new compounds of general formula [M(N3)2(dmbpy)] in which dmbpy = 5,5′-dimethyl-2,2′-bipyridine, and M = Mn(II) or Co(II), have been solvothermally synthesized and characterized structurally and magnetically. The structures consist of zig-zag polymeric chains with alternating bis-µ(azide-N1)2M and bis-µ(azide-N1,N3)2M units in which the cis-octahedrally based coordination geometry is completed by the N,N’-chelating ligand dmbpy. The molecular structures are basically the same for each metal. The Mn(II) compound has a slightly different packing mode compared to the Co(II) compound, resulting from their different space groups. Interestingly, relatively weak interchain interactions are present in both compounds and this originates from π–π stacking between the dmbpy rings. The magnetic properties of both compounds have been investigated down to 2 K. The measurements indicate that the manganese compound shows spin-canted antiferromagnetic ordering with a Néel temperature of TN = 3.4 K and further, a field-induced magnetic transition of metamagnetism at temperatures below the TN. This finding affords the first example of an 1D Mn(II) compound with alternating double end-on (EO) and double end-to-end (EE) azido-bridged ligands, showing the coexistence of spin canting and metamagnetism. The cobalt compound shows a weak ferromagnetism resulting from a spin-canted antiferromagnetism and long-range magnetic ordering with a critical temperature, TC = 16.2 K.